Optimisation and use of humanised RBL NF-AT-GFP and NF-AT-DsRed reporter cell lines suitable for high-throughput scale detection of allergic sensitisation in array format and identification of the ECM–Integrin interaction as critical factor - Wang, Xiaowei; Cato, Paul; Lin, Hsiu-Chen; Li, Tongen; Wan, Daniel; Alcocer, Marcos J.C.; Falcone, Franco H. (Humana Press, 2014)
We have previously described a microarray platform combining live basophils with protein arrays suitable for high-throughput detection of sensitisation against allergens. During optimisation of this technique, we observed severe losses of adhering cells during the washing steps, particularly after activation. In order to preserve cell binding, we tested the cell adhesion characteristics of different extracellular matrix proteins: human collagen I, fibronectin (FN) from bovine plasma and laminin (LN). FN was more effective than LN and collagen. Cell detachment after activation was in part due to reduced surface expression of VLA-4, the main ligand for FN, which was significantly decreased within 15 min of stimulation with 1 μg/mL calcium ionophore A23187, reaching a minimum after 2 h then slowly recovering. These optimised conditions were used for testing of well-characterised sera from allergic patients using two newly developed rat basophil leukaemia stable reporter cell lines (RBL NF-AT/GFP and RBL NF-AT/DsRed), which both express the human high-affinity IgE receptor alpha chain (FcεRIα). Both cell lines were able to detect sensitisation to specific allergens showing the expected bell-shaped dose–response curve, and correlated (R 2 = 0.75) with the standard beta-hexosaminidase assay, which is not suitable for an array format.